2006
DOI: 10.1002/jcp.20945
|View full text |Cite
|
Sign up to set email alerts
|

Murine allogeneic in vivo stem cell homing,

Abstract: Stem cell homing has been studied in syngeneic models and appears to be rapid (<1 h) and dependent on cellular adhesion and migration factors. We utilized a full H2-mismatched transplantation model to determine the basics of allogeneic homing. C57BL/6J Lin-Sca-1+ cells were labeled with CFSE and injected in non-myeloablated BALB/c mice. Fluorescent cell detection was via high-speed FACS analysis. Alternatively, B6.SJL whole bone marrow cells were injected in lethally irradiated BALB/ c mice (10 Gy). One, 3, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
2
16
1
Order By: Relevance
“…Other studies demonstrate that HSC could be also found in bone marrow and peripheral blood 1 h after their injection [19]. However, the current work demonstrates that fluorescent labeled cells were found in spleen tissue only after 4 hours of inoculation.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Other studies demonstrate that HSC could be also found in bone marrow and peripheral blood 1 h after their injection [19]. However, the current work demonstrates that fluorescent labeled cells were found in spleen tissue only after 4 hours of inoculation.…”
Section: Resultscontrasting
confidence: 63%
“…Using kidney damage model it was found out that inoculated HSC were detected in kidney tissue following 24 hours of treatment [7]. Colvin et al [19] stated that after three hours of inoculation the stem cells were not found in peripheral blood. Our study revealed that hematopoietic lin -cells could stay in liver tissue for 48 hours, in spleen and paw edema at least for 72 hours.…”
Section: Resultsmentioning
confidence: 99%
“…We petitive host HSC pool that can be easily replaced by donor HSCs (34,35). Homing efficiency was assessed 24 h post-transplantation in the bone marrow, peripheral blood, and spleen of the recipient mice.…”
Section: Fgf-23 Deficiency Alters Early Hematopoietic Progenitors-mentioning
confidence: 99%
“…CFU-GM was 918.7±47.82 in the group of non-irradiated mice. There was significant increase of CFU-GM in the spleen of non-irradiated mice -29.8±19.23 CFU-GM for 10 5 The data reported of mean±SD (standard deviation of the mean)colonies of CFU-GM (granulocyte-macrophage colonyforming unit cells). * Differences in the hematopoietic recovery of the total number colony CFU-GMx10 5 MNC (mononuclear cells) is significant (p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…It means that the process of bone marrow repair and hematopoiesis reconstitution is also associated with more extensive reparation processes and with issues such as homing of transplated cells, much discussed at present (15,5). Our experiments were aimed at hematopoetic rescue of transplanted CD117 + (lacZ + ) cells sorted from bone marrow after whole-body (WB) lethally irradiated mice.…”
Section: Discussionmentioning
confidence: 99%